Pengaruh Leverage, Profitabilitas, dan Likuiditas terhadap Earning Response Coefficient (ERC) pada PT BSI Tbk - Riky Dermawan Sipahutar; Yusrizal Yusrizal; Nur Ahmadi Bi Rahmani (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to empirically examine the effect of Leverage, Profitability, and Liquidity on the Earning Response Coefficient (ERC) in Islamic banking companies. Data collection techniques using documentation and data analysis techniques using purposive sampling. Earning Response Coefficient (ERC) is a type of dependent variable that can be useful in research. However, the variables that are independent in this research are Leverage, Profitability, and Liquidity. The method used in this research is multiple linear regression analysis. This study uses a tool that is IBM SPSS Statistics 20 software program. The results of this study can be interpreted that simultaneously there is a positive and significant direct effect, namely Leverage, Profitability, and Liquidity on the Earning Response Coefficient. While partially Leverage has a significant negative effect on the Earning Response Coefficient, profitability has a significant positive effect on the Earning Response Coefficient, liquidity has no significant effect on the Earning Response Coefficient. Keywords: Leverage, Profitability, Liquidity, Earning Response Coefficient (ERC), Bank Syariah Indonesia.